MyGift volunteers distribute nasi lemak for breakfast - Siti Nurfarmy, Ibrahim (2019)
Starting 1 October 2019, a total of 400 packs of nasi lemak were distributed simultaneously at both campuses to ease the burden of the students of Universiti Malaysia Pahang (UMP) before starting their early morning classes.